Zümmögő könyvtár: Három angol nyelvű kortárs költő Horatiusa (Billy Collins, Donald Hall, Harry Eyres) - Kőrizs, Imre (Studia Litteraria, 2022)
This paper focuses on three English-speaking contemporary poets, especially on the image of the classical Latin and Greek cultures appearing in their works. In Billy Collins’ works the elements of traditional Euro-Atlantic high culture – mainly the classical antiquity, France and Italy—play an important role, alongside some echoes of Japanese and Chinese cultures. From a certain point of view, one can call Collins ‘a poet of poetry’, as his poems often focus on the process of writing, on the poetic effect and tradition. His particular attitude towards the ancient heritage (philosophy, architecture, art, literature, genres, tones and themes) makes Collins a sort of Horatian poet, as he seems to share—particularly in poems talking about the effect of passing time—his ancient predecessor’s melancholy, wit and irony. In the second part of the paper a book of Donald Hall is analyzed: The Museum of Clear Ideas pays homage to Horace, in particular in its second part, which is a contemporary remake of Horace’s Carmina’s whole Book I, and occasionally shows influence of social and political criticism. e third and last part of the paper is about the rather unusual book by Harry Eyres about Horace (Horace and Me). It is a kind of ‘parallel lives’, the life of ‘Harry and Horry’, as one of the book reviewers puts it. Eyres, educated in Eton and Cambridge, a poet, wine critic and cultural journalist brings Horace closer to the modern reader by analyzing and translating his poems in a fresh way, not avoiding personal approaches and modern references.